Properties of Irrigated Boz-Meadow Soils of Syrdarya Region (Texas Journal of Agriculture and Biological Sciences, 2022)
The article analyzes the current state of the mechanical composition, agrophysical and agrochemical properties of irrigated gray-meadow soils of the Syrdarya region. Under the conditions of irrigated agriculture, the physical, water-physical, thermo physical and physical-mechanical properties of soils are of great importance in increasing the productivity of soils. The consumption and mobility of soil moisture and the assimilation of nutrients are determined by physical and water-physical properties, and the quality of soil cultivation is determined by physical and mechanical properties. The presence of these factors within acceptable limits leads to better growth and development of crops, as well as increased yields. According to the data obtained, it was found that the volumetric mass of the soil is 1.39-1.45 g/cm3 , and the presence of an arable layer at a low level is due to the effect of cultivation